2022
DOI: 10.1177/20503121221083207
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and causes of intestinal obstruction in Ethiopia: A systematic review

Abstract: Objective: This systematic review was aimed to address the prevalence and causes of intestinal obstruction in Ethiopia. Methods: Systematic searches were conducted on PubMed, EMBASE, CINAHL, Scopus, African Journals Online, HINARI, and other supplementary sources, including Google Scholar. We conducted methodological quality assessments for the articles by employing a critical appraisal checklist of Joanna Briggs Institute. Results: The reported prevalence of intestinal obstruction in Ethiopia ranges from 18.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
(154 reference statements)
0
11
0
Order By: Relevance
“…Bowel knots are the unusual causes for bowel obstruction among others ileo-ileal knotting are the rarest reported causes for SBO.In my knowledge and review only 14 such cases were reported worldwide and only 3 cases in Ethiopia all of which were managed in specialized hospitals and managed by specialist physicians. (1,2,3) But in our case it was managed in one of our district hospital in Ethiopia and the leading surgeon was IESO who is a holder of MSc in integrated emergency surgery,dully known in Ethiopia and licensed to do obstetrics,gynecology and general surgical emergencies. For last 10yrs IESOs in Ethiopia were performing tremendous emergency surgical activities in primary health institutions in the country where still the physician specialists are scarce.…”
Section: Discussionmentioning
confidence: 87%
“…Bowel knots are the unusual causes for bowel obstruction among others ileo-ileal knotting are the rarest reported causes for SBO.In my knowledge and review only 14 such cases were reported worldwide and only 3 cases in Ethiopia all of which were managed in specialized hospitals and managed by specialist physicians. (1,2,3) But in our case it was managed in one of our district hospital in Ethiopia and the leading surgeon was IESO who is a holder of MSc in integrated emergency surgery,dully known in Ethiopia and licensed to do obstetrics,gynecology and general surgical emergencies. For last 10yrs IESOs in Ethiopia were performing tremendous emergency surgical activities in primary health institutions in the country where still the physician specialists are scarce.…”
Section: Discussionmentioning
confidence: 87%
“…Intestinal obstruction is one of the commonest causes of acute abdomen carrying significant mortality if not intervened timely. In a systematic review done among Ethiopian hospitals, the prevalence of bowel obstruction ranges from 18 to 50 % among patients with acute abdomen [8] . Sigmoid volvulus is one of the common causes of large bowel obstruction more happening in the adults and elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion for small bowel and carcinoma for large bowel are commonest causes of obstruction in developed nations but volvulus is commonest cause of obstruction in countries like Ethiopia which may be related to the dietary habit [6] , [7] . Sigmoid volvulus is the commonest cause of large bowel obstruction in Africa and particularly in Ethiopia [8] . Sigmoid volvulus can develop years after suboptimal resectional treatment for sigmoid volvulus [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Ileosigmoid knotting is the commonest and ileoileal knotting is the unusual and only reported in few cases. (1,3) District hospitals in Ethiopia are primary level hospitals and usually the surgical unit is lead by Integrated Emergency surgical o cers( IESO) who is dully known in Ethiopia and the IESO is a postgraduate professional trained for 3yrs and authorized to do emergency obstetrics, gynecologic and emergency general surgeries. It was task shifting professional license allowing to do emergency surgeries in district Ethiopian hospitals where there is scarce physician specialists.…”
Section: Introductionmentioning
confidence: 99%